Comparative structural, digestion and absorption characterization of three common extruded plant proteins - Wang, Yuxiang; Zheng, Zhaojun; Zhang, Chaoyang; Wu, Cong; Tan, Chin-Ping; Liu, Yuanfa (Elsevier, 2024)
Extruded plant proteins, also known as textured vegetable proteins (TVPs), serve as vital components in plant-based meat analogue, yet their structural and nutritional characteristics remain elusive. In this study, we examined the impact of high-moisture (HM) and low-moisture (LM) extrusion on the structures, digestion and absorption of three types of plant proteins. Extrusion transformed plant proteins from spherical to fibrous forms, and formed larger aggregate particles. It also led to the disruption of original disulfide bonds and hydrophobic interactions within protein molecules, and the formation of new cross-links. Intriguingly, compared to native plant proteins, TVPs’ α-helix/β-sheet values decreased from 0.68 to 0.69 to 0.56–0.65. Extrusion increased the proportion of peptides shorter than 1 kD in digesta of TVPs by 1.44–23.63. In comparison to unextruded plant proteins, TVPs exhibited lower content of free amino acids in cell transport products. Our findings demonstrated that extrusion can modify protein secondary structure by diminishing the α-helix/β-sheet value, and impact protein tertiary structure by reducing disulfide bonds and hydrophobic interactions, promoting the digestion and absorption of plant proteins. These insights offer valuable scientific backing for the utilization of extruded plant-based proteins, bolstering their role in enhancing the palatability and nutritional profile of plant-based meat substitutes. © 2023 Elsevier Ltd